Correlation of Difficulty in Emotional Regulation with BehavioralProblems Among Young Children in Both Private and PublicSectors Educational Institutions of Swabi (Journal of Asian Development Studies, 2024)
Emotional regulation is the essential skill that enables people to effectively control their emotions and behaviors. It is crucial for young children, in particular, because they are still developing their capacity for passionate direction. The capacity to control one's emotions in a way that is bothadaptive and acceptable in society is known as emotional regulation. This study used an analytical cross-sectional design to find the correlation between difficulty in emotional regulation and behavioral problems. It also used a purposive sampling technique to collect data from 400 childrenof both sexes at public and private schools. Most of the study participants were male, in the age range of 7-9. In regards to birth order, most of the study participants (38%) were firstborn, followed by second born (30%) and lastborn (26.5%); however, the only children accounted for merely 5%. The Pearson correlation test was run to find the correlation between difficulty in emotional regulation and behavioral problems in this study. The test value was 0.42, and the pvalue was less than 0.05, indicating that emotional regulation difficulty has a positive correlation with behavioral problems. The current study's evidence strongly suggests that emotional  regulation can assist in treating behavioral issues in young children. The study's findings show that emotional problems correlate negatively with emotional regulation, whereas behavioral problems correlate positively with emotional regulation difficulties. This suggests that enhancing emotional regulation may lessen behavioral problems in children.